The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnmol.2019.00315
|View full text |Cite
|
Sign up to set email alerts
|

KLHL1 Controls CaV3.2 Expression in DRG Neurons and Mechanical Sensitivity to Pain

Abstract: Dorsal root ganglion (DRG) neurons process pain signaling through specialized nociceptors located in their peripheral endings. It has long been established low voltage-activated (LVA) Ca V 3.2 calcium channels control neuronal excitability during sensory perception in these neurons. Silencing Ca V 3.2 activity with antisense RNA or genetic ablation results in anti-nociceptive, anti-hyperalgesic and anti-allodynic effects. Ca V 3.2 channels are regulated by many proteins (Weiss and Zamponi, 2017), including KLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…The activity dynamics of GABAergic neurons in different hypothalamic regions, including ARH [ 28 , 29 ], lateral hypothalamus (LH) [ 30 , 31 ], tuberal nucleus (TN) [ 32 , 33 ], and zona incerta (ZI) [ 34 , 35 ], plays a vital role in the regulation of feeding behavior, body weight, and energy expenditure. It has been demonstrated that neural excitability is regulated by subtypes of neuronal voltage-activated Ca 2+ channels, including CAV3.2 [ 36 , 37 ]. CAV3.2 may serve as a critical intrinsic modulator for the neural excitability of hypothalamic GABAergic neurons to control energy homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…The activity dynamics of GABAergic neurons in different hypothalamic regions, including ARH [ 28 , 29 ], lateral hypothalamus (LH) [ 30 , 31 ], tuberal nucleus (TN) [ 32 , 33 ], and zona incerta (ZI) [ 34 , 35 ], plays a vital role in the regulation of feeding behavior, body weight, and energy expenditure. It has been demonstrated that neural excitability is regulated by subtypes of neuronal voltage-activated Ca 2+ channels, including CAV3.2 [ 36 , 37 ]. CAV3.2 may serve as a critical intrinsic modulator for the neural excitability of hypothalamic GABAergic neurons to control energy homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…KLHL1 KO mice display similar alterations but they also exhibit compensatory expression to sustain calcium current homeostasis in hippocampal neurons, yet they still display synaptic alterations ( Perissinotti et al, 2015 ). Moreover, DRG neurons from KLHL1 KO mice exhibit and uncompensated reduction of Ca V 3.2 expression, resulting in reduced neuron excitability and decreased sensitivity to pain ( Martínez-Hernández et al, 2020 ). Thus, deletion of KLHL1 results in differential alteration of calcium currents and neuronal excitability depending on their role in specific nervous system areas.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 46 , 75 Although our studies have initially focused on testing whether targeting IDRs can facilitate discovery of T-type/Ca V 3.2 inhibitory peptides for AAV-mediated analgesia, how the identified Ca V 3.2iPA functioning remains unknown. The potential signaling pathways that the Ca V 3.2iPAs affected could be many because Ca V 3.2 intracellular segments serve as essential interfaces for many regulatory signaling molecules, including nuclear-localized deubiquitinating enzyme (USP5), 29 calcium/calmodulin–dependent protein kinase II, 35 cyclin-dependent kinase 5, 32 G-proteins, 64 calcineurin, 34 calmodulin, 15 syntaxin/SNAP25, 83 Kelch-like protein 1, 50 and Stac1. 74 In addition, Ca V 3.2 can form protein complexes with members of the K + channel family, such as K V 4, K Ca3.1 , and K Ca1.1 (BK), 2 , 70 and K + /Na + hyperpolarization–activated cyclic nucleotide-gated channel 1, 22 as well as lipids.…”
Section: Discussionmentioning
confidence: 99%